2017
DOI: 10.1247/csf.16023
|View full text |Cite
|
Sign up to set email alerts
|

TFE3, HSP47, and CREB3 Pathways of the Mammalian Golgi Stress Response

Abstract: ABSTRACT. The capacity of each organelle in eukaryotic cells is tightly regulated in accordance with cellular demands by specific regulatory systems, which are generically termed organelle autoregulation. The Golgi stress response is one of the systems of organelle autoregulation and it augments the capacity of Golgi function if this becomes insufficient (Golgi stress). Recently, several pathways of the mammalian Golgi stress response have been identified, specifically the TFE3, HSP47, and CREB3 pathways. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
80
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 49 publications
1
80
0
Order By: Relevance
“…Recently, certain stresses that disrupt the Golgi structures and functions were defined as Golgi stress [16,17], although this concept is still ambiguous in comparison with ER stress, and the whole picture has not yet been clarified. Following treatment with Nigr, which is often used to trigger Golgi stress [18], the full-length CREB3 protein was depleted, but levels of the cleaved form of CREB3 were negligible in HEK293 cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, certain stresses that disrupt the Golgi structures and functions were defined as Golgi stress [16,17], although this concept is still ambiguous in comparison with ER stress, and the whole picture has not yet been clarified. Following treatment with Nigr, which is often used to trigger Golgi stress [18], the full-length CREB3 protein was depleted, but levels of the cleaved form of CREB3 were negligible in HEK293 cells.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we tested eight reagents to monitor endogenous CREB3 cleavage and found that BFA and Mone induced CREB3 processing in a time-dependent manner. Among members of the CREB3/ATF6 family, CREB3 activation occurs in response to Golgi stress; however, the concept and machinery of Golgi stress [16,17,27] are still obscure in comparison with those of ER stress. In particular, it is unclear whether Golgi stress is a common target of BFA and Mone (a sodium ionophore) since their pharmacological actions are not identical.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these secretory and polarity functions, the Golgi has emerged as a versatile platform that supports a broad range of cellular processes. The Golgi can actively modulate the microtubule network [19,20], forms a hub for a variety of signaling pathways [2124] and participates in the regulation of calcium and pH homeostasis [25], stress response [26,27], apoptosis [28] and autophagy [29,30**]. …”
Section: Structure and Function Of The Golgi Apparatusmentioning
confidence: 99%
“…Like the ER, the Golgi can be stressed under prolonged anti‐HIV drug use and initiates Golgi stress response, which involves a few regulating factors/pathways: TFE3, CREB3‐ARF4 pathway, and HSP47. ( 19,20 ) TFE3 regulates transcriptional activation of genes encoding vesicular trafficking components or Golgi resident enzymes. The CREB3‐ARF4 pathway involves both ER and Golgi, in which ARF4 is a member of the small GTPase family that regulates Golgi‐to‐ER vesicular trafficking.…”
mentioning
confidence: 99%